2008
DOI: 10.1007/s12070-008-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of nasal mucosa in endoscopic sinus surgery and its correlation to electron microscopy of cilia

Abstract: The effect of functional endoscopic sinus surgery (FESS) was evaluated in 20 patients with chronic sinusitis. The physiological function of sinus mucosa and its mucociliary transport mechanism was assessed pre and post operatively in patients undergoing FESS by performing Saccharin clearance test. The effect of functional sinus surgery on nasal mucosa was evaluated using scanning electron microscopy and study of the ultrastructure of cilia in pre and post operative patients and correlation with histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…On the one hand, certain studies also demonstrated significant improvement of mucosal appearance 6 months after surgery. Particularly, a substantial decrease in mucosal edema, inflammation, ulceration, and fibrosis was associated with increased ciliated area, improved ciliary orientation (19) , as well as the reversal of basal membrane thickening and epithelial metaplasia 6 months after surgery (37) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the one hand, certain studies also demonstrated significant improvement of mucosal appearance 6 months after surgery. Particularly, a substantial decrease in mucosal edema, inflammation, ulceration, and fibrosis was associated with increased ciliated area, improved ciliary orientation (19) , as well as the reversal of basal membrane thickening and epithelial metaplasia 6 months after surgery (37) .…”
Section: Discussionmentioning
confidence: 92%
“…The stages of mucosal recovery after FESS include clean cavity (1-2 weeks), mucosal transition (3-10 weeks), and complete epithelization (11-14 weeks) (16) . However, the existing data on timeframes of postoperative mucociliary clearance recovery are highly contradictory, being indicative of 3-4 (17,18) , 6 (19) , or 12 months (20) required for substantial improvement. Moreover, data on pediatric CRS patients are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Sakthikumar et al [4] consisting of 20 patients, the mean pre-operative saccharin test time was found to be 16.20 min with post-operative mean value of 10.30 min. This proved to be highly significant.…”
Section: Discussionmentioning
confidence: 93%
“…It does not require sophisticated equipment to perform the test and can be reproduced. It is neither digested nor metabolised by the body and does not contribute to the daily calorie intake [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In the statistics reviewed, [1][2][3][5][6][7][8][9][10] we found that the sample sizes varied from a minimum of 20 to a maximum of 50. Hence, we (based on feasibility) studied a total of 32 subjects in each of the groups (chronic rhinosinusitis, smokers, and controls); a total of 96 subjects were studied.…”
Section: Methodsmentioning
confidence: 99%